EXPLORING USER NEEDS FOR DIGITAL HEALTH EDUCATION SERVICE IN A MATERNITY AND CHILD HEALTH SETTING - Muiruri, Pennina (My University, 2021)
Health education is an integral part of the services provided by maternity and child health care clinics in Finland. This study aimed to explore and understand the user needs for a digital health education service in maternity and child healthcare in Finland. The main objectives of the study were to explore and identify the challenges and user needs of using the current health education system and explore ideas of how the situation can be improved. The theoretical framework used in this study builds upon concepts, methods, tools, and frameworks from previous studies in user-centered design service design and health education in maternity and child healthcare research. The empirical part was carried out in two phases using primary and secondary qualitative data collection methods. The first phase data collected included research, observations, artifacts, and views of 27 active users of maternity and child healthcare services were collected to understand the context of the project and identify the challenges faced by expectant mothers and young parents. In the second phase, five women from a Swedish mother and child peer group participated in a co-creation workshop to validate the challenges found in phase one of the data collection process and to explore and ideate on the user needs. The results indicate there is an opportunity for maternity and child health care providers to harness the power of digital technology to provide users with information and tools to empower them to better manage their health and health outcomes. There is also an opportunity for healthcare professionals in this field to offer new services and extend the support and care they provide to expectant women and young parents. Service design and user-centered design tools and methods were found to be useful for exploring and finding user needs and are seen as beneficial for future studies in maternity and child health care.
Keywords: health education; service design; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management